Mediterranean drama: pragmatic, legal and moral aspects of hospitality - Nowak, Ewa (Filozofia Publiczna i Edukacja Demokratyczna, 2015)
Hospitality is „not a concept which lends itself to objective knowledge,” Jacques Derrida assumes. His assumption „provokes” and challenges European hospitability, not only in the Mediterranean area in which „welcoming” and „ingratiating” (in Derrida’s terms) forms of human conduct met together thousands years ago, and an asylum seeker found hospitia. What is hospitality and why philosophize about it today? The paper examines hospitality’s pragmatic, customary, legal and moral aspects in, both, historical and contemporary contexts.